Evaluation of the Empirical Scaling Factor of Joule Heating Rates in TIE-GCM With EISCAT Measurements - Günzkofer, Florian Ludwig; Liu, Huixin; Stober, Gunter; Pokhotelov, Dimitry; Borries, Claudia (Earth and Space Science, 2024)
Joule heating is one of the main energy inputs into the thermosphere‐ionosphere system. Precise modeling of this process is essential for any space weather application. Existing thermosphere‐ionosphere models tend to underestimate the actual Joule heating rate quite significantly. The Thermosphere‐Ionosphere‐Electrodynamics General‐Circulation‐Model applies an empirical scaling factor of 1.5 for compensation. We calculate vertical profiles of Joule heating rates from approximately 2,220 hr of measurements with the EISCAT incoherent scatter radar and the corresponding model runs. We investigate model runs with the plasma convection driven by both the Heelis and the Weimer model. The required scaling of the Joule heating profiles is determined with respect to the Kp index, the Kan‐Lee merging electric field EKL, and the magnetic local time. Though the default scaling factor of 1.5 appears to be adequate on average, we find that the required scaling varies strongly with all three parameters ranging from 0.46 to 20 at geomagnetically disturbed and quiet times, respectively. Furthermore, the required scaling is significantly different in runs driven by the Heelis and Weimer model. Adjusting the scaling factor with respect to the Kp index, EKL, the magnetic local time, and the choice of convection model would reduce the difference between Joule heating rates calculated from measurement and model plasma parameters